TINGKAT KELANGSUNGAN HIDUP FRAGMEN KARANG Acroporaformosa YANG DITRANSPLANTASIKAN PADA MEDIA BUATAN YANG TERBUAT DARI PECAHAN KARANG (RUBBLE) - Nur Fadli (BERITA BIOLOGI, 2008)
Coral reefs around the world continue to decline.Corals killed by natural or anthropogenic disturbances are often degraded into rubble. This rubble is dynamic, easily shifted by storms and currents which may forms "killing fields" for coral juveniles, hindering coral recovery. In order to rehabilitate the coral reef, artificial substrates are always used as artificial reefs both for coral transplantation and recruitment. Unfortunately, most artificial substrates are expensive and used material from outside of the ocean (for example concrete/cement base). In order to develop a new low-cost artificial substrate that can be replacing the concrete/cement-base as a media for coral transplantation and coral recruitment, the modified coral rubble were tested in Seribu Islands, Jakarta. Two different net (nylon and polyethylene) were used to form or to shape rubble into a compact shape, stable and strong substrate.The stability of the rubble and the complexity of the surface which is created by the net make this substrate suitable for coral transplantation and coral recruitment. In 6 m, the highest survival was recorded for coral fragments that were transplanted on cement-base (58%). The lowest survival was recorded on nylon + rubble (16%). While, in 10 m, the highest survival was found on cement-base (40%) and the lowest was on polyethylene + rubble (3%). The modified coral rubble is a potential method for coral transplantation and coral recruitment. However, this approach requires testing at additional sites to determine the replicability of the results.